GLP-1 analogues in patients with type 2 diabetes and chronic kidney disease: Benefits beyond glycemic control - Rodrigo Gonçalves Corrêa; Vitória Aparecida Cunha; Marcella Culau Vieira; Mateus de Paula Fonseca Damacena; Natália Elisabeth Wagner Müller; Rafaela dos Santos Bertagli; Rafael Pedro Roewer (International Health Sciences Review, 2026)
Type 2 diabetes and chronic kidney disease form a high-risk cardiorenal phenotype in which treatment goals extend beyond reduction of glycated hemoglobin. This structured narrative, critical, and descriptive review examined PubMed/MEDLINE, the Cochrane Library, and current American Diabetes Association and Kidney Disease: Improving Global Outcomes guidance, prioritizing evidence published from 2011 through August 2026 and including older landmark publications when required. Early cardiovascular outcome trials suggested that glucagon-like peptide-1 receptor agonists reduced albuminuria and atherosclerotic events, but most kidney composites were dominated by new macroalbuminuria and were not designed to test kidney failure. The FLOW trial materially strengthened the evidence by showing that weekly semaglutide reduced clinically important kidney and cardiovascular outcomes and slowed estimated glomerular filtration rate decline in patients with albuminuric chronic kidney disease. Benefits probably arise from combined effects on weight, blood pressure, vascular risk, inflammation, oxidative stress, and renal sodium handling rather than glucose lowering alone. Current evidence supports use of agents with demonstrated benefit within layered therapy that also includes renin-angiotensin system blockade, sodium-glucose cotransporter 2 inhibition, and, when indicated, finerenone. Clinical application requires gradual dose escalation, attention to gastrointestinal intolerance and volume depletion, and individualized decisions in advanced kidney disease.